Changes in the content of monoterpenes in the pine resin in response to damage by Heterobasidion annosum (Fr.) Bref. - Ustskiy, I. M. (Forestry and Forest Melioration, 2019)
Introduction Production of resin in damaged roots is a significant characteristic of the trees damaged by root rot caused by Heterobasidion annosum (Fr.) Bref. and is one of the symptoms of the disease. Resin production is caused by changes in a tree metabolism and its considerable losses in moisture, which also leads to changes in the composition of monoterpenes in essential oils of the resin. Bark beetles may identify the composition of these essential oils by smell, indicating weakened trees and an opportunity to attack them. Thus, in the stand with trees damaged by root rot, bark beetles like Tomicus piniperda L. and T. minor Hart. may attack only trees in the active part of the root rot foci. A rapid spread of the Ips acuminatus bark beetle may be brought about by changes in the composition of essential oils in pine stands as a result of a change in the water regime of trees due to recent climatic fluctuations. The aim of the research was to detect changes in the essential oils of pine trees with varying damage degrees in their root systems in the root rot foci. Materials and Methods Samples of resin were taken from the 4th-grade pine trees growing in Kharkiv Region, damaged by root rot in varying proportions (1–10%, 11–20%, 21–30%, and 31–40%). To determine the damage extent, we excavated the trees’ root systems and measured them. Essential oils were extracted from the resin by steam distillation. The composition of turpentine oils was analyzed by separating them on a LHM-8M gas-liquid chromatograph. We identified monoterpenes by the sequence and time with which the components were coming out of the column. The proportion of the components in essential oils was determined by their peaks part in the total area of the chromatogram. Results and Discussion Trees with the initial stage of the root damage (1–10%) mainly bordered to site with healthy trees. The trees with the root damage of 11–30% grew on the edge of the gap within the disease foci. The most damaged trees (31–40%) were mainly located in the open space of the gap. The results of the study showed that the content of ?-pinene and camphene reduces under the influence of the disease. The trees with the root damage of 11–30%, growing on the edge of the gap, have the least of these components compared to healthy trees. However, the trees with the root damage of 31–40% growing in the open space of the gap have a higher level of monoterpenes compared to that in less damaged trees. We also noted that the content of ?-pinene is 1.8–2 times higher in affected trees compared to healthy ones. The content of ?3-carene in the trees with the root damage of 1–10% or 40% respectively, was 17% and 23% lower compared to healthy trees. It was, on the contrary, 15–16% higher in the trees with 11–30-percent damage, growing in the active part of the root rot focus, compared to healthy trees. The correlation analysis indicated a strong negative relationship between the content of ?-pinene and ?3-carene, namely r0.05 = -0.747. The monoterpenes ?-pinene, ?-pinene, and ?3-carene predominate in resin essential oils. Proportions of other monoterpenes, such as camphene, limonene, dipentene, and ?-cymene are negligible. As a bark beetle attacks trees in the active part of the root rot focus (damage degree 11–30%), both a 70-percent decrease of ?-pinene in the essential oils content and a 15-percent increase of ?3-carene (compared to healthy trees) may serve as a signal and indicate the tree’s weakening, as well as point at the possibility for the tree to be attacked. Conclusions The dynamics of the monoterpenes content in essential oils of resin in trees damaged by root rot (Heterobasidion annosum (Fr.) Bref.), with the progress of the disease depends on both the root damage extent and the position of the tree relative to the active part of the dieback focus. The ?-pinene content is significantly higher in the affected trees and scarcely depends on the progress of the disease. The content of ?-pinene and camphene decreases under the influence of the disease. Their lowest content, as compared with healthy trees, was noted in the trees at the edge of the root rot focus whose roots damage extent was 11–30%. The content of ?3-carene in these trees was 15–16% higher. A strong negative relationship was found between the content of a-pinene and ?3-carene. We came to the conclusion that as bark beetles inhabit the trees growing in the active part of the root rot foci (root damage 11–30%) a 70-percent decrease of a-pinene in the content and a 15-percent increase of ?3-carene (compared with that in healthy trees), may serve as a signal and indicate the possibility for the tree to be attacked. 2 Figs., 2 Tables, 14 Refs.